Development of plant for treatment of working liquids used for process purposes - Trofimov, Igor; Zubchenko, Alexander; Suliman, Aleksey; Maxymov, Sergey (Transport, 2008)
The questions of working liquids treatment using different methods are considered in this paper. Improved electric separator and hydraulic cyclone are developed for cleaning the liquids from mechanical impurities; the mobile unit is designed for cleaning the working liquids using the force fields. The results of experimental research of the aforementioned unit are represented.First published online: 27 Oct 2010